Strategi Manajemen Talenta Dalam Meningkatkan Kualitas Pementasan Talent Bali Entertainments Agency - Erina, Isobe; Wirata, I Nengah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
This study explores the talent management strategies implemented by Bali Entertainments Agency (BA) to enhance the performance quality of its talents, particularly dancers, amid the increasingly competitive entertainment industry in Bali. Employing a qualitative approach with SWOT analysis, data were gathered through in- depth interviews with management and talents, direct observations, and document reviews. The findings reveal BA’s strengths in recruiting experienced talents, maintaining costume originality, ensuring flexibility, and fostering strong teamwork; its main weaknesses include limited staff during peak demand and insufficient regular training; opportunities arise from service diversification and the utilization of digital media; while the key threats are price competition and shifting event trends. Recommended strategies include strengthening training programs, selective recruitment, diversifying event portfolios, and reinforcing branding to maintain quality standards and talent loyalty.